Body-composition assessment via air-displacement plethysmography in adults and children: a review - Fields, David A; Goran, Michael I; McCrory, Megan A (The American journal of clinical nutrition, 2002)
Laboratory-based body-composition techniques include hydrostatic weighing (HW), dual-energy X-ray absorptiometry (DXA), measurement of total body water (TBW) by isotope dilution, measurement of total body potassium, and multicompartment models. Although these reference methods are used routinely, each has inherent practical limitations. Whole-body air-displacement plethysmography is a new practical alternative to these more traditional body-composition methods. We reviewed the principal findings from studies published between December 1995 and August 2001 that compared the BOD POD method (Life Measurement, Inc, Concord, CA) with reference methods and summarized factors contributing to the different study findings. The average of the study means indicates that the BOD POD and HW agree within 1% body fat (BF) for adults and children, whereas the BOD POD and DXA agree within 1% BF for adults and 2% BF for children. Few studies have compared the BOD POD with multicompartment models; those that have suggest a similar average underestimation of approximate 2-3% BF by both the BOD POD and HW. Individual variations between 2-compartment models compared with DXA and 4 -compartment models are partly attributable to deviations from the assumed chemical composition of the body. Wide variations among study means, -4.0% to 1.9% BF for BOD POD - HW and -3.0% to 1.7% BF for BOD POD - DXA, are likely due in part to differences in laboratory equipment, study design, and subject characteristics and in some cases to failure to follow the manufacturer's recommended protocol. Wide intersubject variations between methods are partly attributed to technical precision and biological error but to a large extent remain unexplained. On the basis of this review, future research goals are suggested.